2018
DOI: 10.1021/acs.chemrestox.8b00250
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Human Aldo-Keto Reductases in the Metabolic Activation of the Carcinogenic Air Pollutant 3-Nitrobenzanthrone

Abstract: 3-Nitrobenzanthrone (3-NBA) is a potent mutagen and suspected human carcinogen detected in diesel exhaust particulate and ambient air pollution. It requires metabolic activation via nitroreduction to promote DNA adduct formation and tumorigenesis. NAD(P)H:quinone oxidoreductase 1 (NQO1) has been previously implicated as the major nitroreductase responsible for 3-NBA activation, but it has recently been reported that human aldo-keto reductase 1C3 (AKR1C3) displays nitroreductase activity toward the chemotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 90 publications
0
25
1
Order By: Relevance
“…Among the human genes regulated by NRF2, AKR1C1–1C3 and NQO1 are consistently the most overexpressed in response to pharmacological activators of NRF2 and by activation of NRF2 by KEAP1 knockdown. , The metabolic activation of 3-NBA requires nitroreduction by these enzymes in human lung cells where 34% of 3-NBA nitroreduction is attributed to AKR1C1–1C3 and up to 40% is attributed to NQO1 . Given the importance of AKR1C1–1C3 and NQO1 nitroreductase activity, we sought to determine the role of NRF2-KEAP1 signaling on 3-NBA toxication in vitro as measured by 3-ABA formation, cell viability, and cytotoxicity in two human lung cell lines: A549 cells that harbor somatic mutations in KEAP1 and epigenetic silencing of its promoter which lead to high consititutive NRF2 expression and HBEC3-KT cells with wildtype KEAP1 that are sensitive to NRF2 activators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the human genes regulated by NRF2, AKR1C1–1C3 and NQO1 are consistently the most overexpressed in response to pharmacological activators of NRF2 and by activation of NRF2 by KEAP1 knockdown. , The metabolic activation of 3-NBA requires nitroreduction by these enzymes in human lung cells where 34% of 3-NBA nitroreduction is attributed to AKR1C1–1C3 and up to 40% is attributed to NQO1 . Given the importance of AKR1C1–1C3 and NQO1 nitroreductase activity, we sought to determine the role of NRF2-KEAP1 signaling on 3-NBA toxication in vitro as measured by 3-ABA formation, cell viability, and cytotoxicity in two human lung cell lines: A549 cells that harbor somatic mutations in KEAP1 and epigenetic silencing of its promoter which lead to high consititutive NRF2 expression and HBEC3-KT cells with wildtype KEAP1 that are sensitive to NRF2 activators.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence of 3-ABA was used to measure the nitroreduction of nonfluorescent 3-NBA in cell culture as published previously . To assess the contribution of NRF2 signaling in the metabolic activation of 3-NBA, experiments were conducted in various A549 cell lines (A549 wt, A549 NRF2-Het, and A549 NRF2-KO).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the metabolic activation of the chemotherapeutic agent PR-104A using transfected cDNAs showed that surprisingly AKR1C3 and not NQO1 was the major NTR involved in its bioactivation . The NTR activity of AKR1C3 has since been expanded to include the nitroarenes, 3-nitrobenzanthrone and 1-NP . The AKRs catalyze an ordered bi−bi kinetic mechanism in which the NADPH is the first substrate to bind and NADP + is last to leave. , The final products of these reactions are amines, and the formation of the intermediate nitroso- and hydroxylamino compounds is difficult to observe and may be related to their rapid propensity to undergo further reduction.…”
Section: Mammalian Nitroreductasesmentioning
confidence: 99%